Pulmonary Contussion in a Free Ranging Sloth Bear (Melursusursinus)- A Case Report - Harane, Ranjeet; Rokde, Amol; Chitariya, Jhanvi; Rajput, Nidhi; Shrivastav, AB (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The sloth bear (melursus ursinus) belongs to family Ursidae and it is endemic to Indian subcontinent. Sloth bear is completely protected under schedule I of the Indian Wildlife (Protection) Act, 1972 and listed as vulnerable species in the World Conservation Union’s Red List of Threatened Animals and also listed under Appendix I of CITES (Garshelis et al., 1999). Severe blow on chest by blunt object and leakage of blood from capillaries caused accumulation of blood in lung parenchyma , resulted into a condition known as Pulmonary contusion. The accumulation in the lung tissue interferes with efficiency of alveoli and bronchioles for gas exchange, potentially leading to inadequate oxygen levels (hypoxia) and death. A rare case of a pulmonary contussion has been noticed during routine post-mortem examination at School of Wildlife Forensic and Health, Jabalpur, (M.P.)